(untitled) (Per Musi, 2017)
This article introduces an approach to popular song that combines socio‐historic analysis – which discusses the relationship between the work and its social environment – with the musical‐linguistic‐discursive aspects of its inner structure. It also seeks to identify and analyse the elements responsible for the production of musical aesthetic responses. Firstly, the work introduces a series of theoretical frames of reference based on the works of Antonio Candido, Lev S. Vigotski, Carlos Sandroni, Simha Arom and Godfried Toussaint. Secondly, we will analyse a particular case: the samba Portela na avenida by Mauro Duarte and Paulo César Pinheiro, popularized in recording by Clara Nunes.